Enhancing Application Monitoring Through AI-Driven Alert Correlation - Vaidyanathan Sivakumaran (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of AI-driven alert correlation systems in modern application monitoring environments. The article examines the transformation from traditional monitoring approaches to sophisticated AI-powered solutions, highlighting key challenges and advancements in alert management. It explores the impact of artificial intelligence on various aspects of monitoring, including pattern recognition, dynamic thresholds, and automated response mechanisms. The article demonstrates how AI-driven correlation techniques have revolutionized incident detection, root cause analysis, and overall operational efficiency. Through a detailed examination of best practices and technical requirements, the article provides insights into successful implementation strategies while exploring future trends in AI-powered monitoring solutions.